Implementing softwae configuration management for CDMA project in motorola GSG Malaysia - Mohamad Hamzi Abdul Azziz, author; Norbik Bashah Idris, supervisor; Fakulti Sains Komputer dan Sistem Maklumat (Kuala Lumpur : Universiti Teknologi Malaysia, 2003)
Thesis (Sarjana Sains (Real Time Software Engineering)) - Universiti Teknologi Malaysia, 2003